METHOD FOR CODING DIAGONAL NON-UNIFORM POSITIONAL NUMBERS FOR THE COMPRESSION OF BASIC FRAMES OF THE VIDEO STREAM IN INFOCOMMUNICATION SYSTEMS - Бараннік, В. В.; Отман Шаді, О. Ю. (Science-based technologies, 2014)
It is shown that the actual direction of researches is lowering of intensity of code representation of basic frames of a video stream. The model of an assessment of informtiveness of a transform is created taking into account that the transform of the discrete cosine representation, is considered on non-uniform diagonal structure, and represents combinatorial object. It is justified that in the conditions of existence of a tendency in change of properties of a transform in the diagonal direction for a non-uniform and diagonal method of detection of dynamic ranges the potential of rather additional elimination of structural redundance in images is provided. Development of a method of lowering of intensity of code representation of basic frames on the basis of diagonal and non-uniform positional coding of transforms is explained. Creation of the generalized technology of code representation of diagonals without prior information on its length and sequence number in a transform is considered. The technology of a kodoobrazovaniye to codegrams on the basis of the diagonal and non-uniform principle of separation of quantity of discharges on the basis of information on length of number and its base is developed.